Dietary Carotenoids and Cognitive Decline: A Longitudinal Study Among Chinese Middle‐Aged and Older Adults - Liyan Huang; Ting Shen; Minyu Wu; Yiying Gong; Gulisiya Hailili; Ziping Wang; Caifeng Zhao; Wei Chen; Shuang Rong; Changzheng Yuan (Health Care Science, 2026)
ABSTRACT Background This study examined the association between dietary intakes of total and specific carotenoids and cognitive decline among Chinese middle‐aged and older adults. Methods We included 4043 participants aged 55 years and older from the China Health and Nutrition Survey (1997–2006). Average daily dietary intakes of total carotenoids, α‐carotene, β‐carotene, β‐cryptoxanthin, lycopene, and lutein + zeaxanthin were calculated from 3‐day 24‐h dietary recalls. Cognitive function was measured repeatedly using the Telephone Interview for Cognitive Status‐Modified. Linear mixed‐effects models were utilized to estimate beta coefficients ( β ) and the 95% confidence intervals (CIs) for the association of energy‐adjusted carotenoid intake with changes in cognitive z ‐scores. Results Higher intake of total dietary carotenoids was associated with slower cognitive decline. Comparing the top to bottom quintiles (median intake: 37.0 vs. 3.1 mg/day) of total carotenoids, the adjusted difference in annual decline rates (95% CI) was 0.018 (0.001–0.035, p ‐trend = 0.037). The strongest association was observed for moderate intake at the fourth quintile (median intake: 23.5 mg/day, β = 0.028, 95% CI: 0.011–0.046, p ‐quadratic = 0.030). Protective associations were also found for specific carotenoids, including α‐carotene ( β Q5 vs. Q1 = 0.037, 95% CI: 0.020–0.055), β‐cryptoxanthin ( β = 0.032, 95% CI: 0.014–0.049), lutein + zeaxanthin ( β = 0.020, 95% CI: 0.002–0.037), lycopene ( β = 0.018, 95% CI: 0.001–0.035) and β‐carotene ( β = 0.019, 95% CI: 0.001–0.036). Conclusions A potential nonlinear association between dietary carotenoids and cognitive decline was observed in Chinese middle‐aged and older adults. Further research is warranted to confirm optimal intake level for dietary carotenoids and to investigate the underlying biological mechanisms.